Do All Opioid Drugs Share the Same Immunomodulatory Properties? A Review From Animal and Human Studies - Franchi, Silvia; Moschetti, Giorgia; Amodeo, Giada; Sacerdote, Paola (Frontiers in Immunology, 2019)
Suppression of the immune system has been constantly reported in the last years as a classical side effect of opioid drugs. Most of the studies on the immunological properties of opioids refer to morphine. Although morphine remains the “reference molecule”, other semisynthetic and synthetic opioids are frequently used in the clinical practice. The primary objective of this review is to analyze the available literature on the immunomodulating properties of opioid drugs different from morphine in preclinical models and in the human. A search strategy was conducted in PubMed, Embase, and the Cochrane databases using the terms “immunosuppression,” “immune system,” “opioids”, “Natural killer cells”, “cytokines” and “lymphocytes” The results achieved concerning the effects of fentanyl, methadone, oxycodone, buprenorphine, remifentanil, tramadol and tapentadol on immune responses in animal studies, in healthy volunteers and in patients are reported. With some limitations due to the different methods used to measure immune system parameters, the large range of opioid doses and the relatively scarce number of participants in the available studies, we conclude that it is not correct to generalize immunosuppression as a common side effect of all opioid molecules.